Cross-sectional study on relationships between physical function and psychological readiness to return to sport after anterior cruciate ligament reconstruction - Junya Aizawa; Kenji Hirohata; Shunsuke Ohji; Takehiro Ohmi; Sho Mitomo; Hideyuki Koga; Kazuyoshi Yagishita (BMC, 2022)
Abstract Background Information about specific factors of physical function that contribute to psychological readiness is needed to plan rehabilitation for a return to sports. The purpose of this study was to identify specific physical functions related to the psychological readiness of patients aiming to return to sports 6 months after reconstruction. We hypothesized that the knee strength is a factor related to the Anterior Cruciate Ligament-Return to Sport after Injury scale (ACL-RSI) cutoff score for a return to sports. Methods This was a cross-sectional study. Fifty-four patients who had undergone primary reconstruction using hamstring tendon participated in this study. Psychological readiness was measured using the ACL-RSI in patients at 6 months after reconstruction. To identify specific physical functions related to the ACL-RSI score, participants were divided into groups with ACL-RSI scores of ≥ 60 or < 60. Non-paired t-tests or the Mann-Whitney test were performed to analyze group differences in objective variables in physical function: (1) knee strength in both legs; (2) leg anterior reach distance on both sides; and (3) single-leg hop (SLH) distances in three directions for both legs. Results Significant differences between groups were identified in knee flexion strength (60°/s) for the uninvolved limb, hamstring-to-quadriceps ratio (60°/s) for the uninvolved limb, knee flexion strength (180°/s) for the involved limb, limb symmetry index (LSI) of leg anterior reach distance, the ratio of the distance to the height of the patient and LSI of SLH distances in lateral and medial directions. Conclusion This study revealed that at 6 months after reconstruction, increased knee flexion strength (ratio of peak torque measured to body mass of the patient), hamstring-to-quadriceps ratio, leg anterior reach distance LSI, and lateral and medial SLH appear important to exceed the ACL-RSI cutoff for a return to sports. The present results may be useful for planning post-operative rehabilitation for long-term return to sports after reconstruction.